A preceptorship model to facilitate clinical nursing education in health training institutions in Botswana - Antonia Dube; Mahlasela A. Rakhudu (AOSIS, 2021)
Background: Despite the wide use of preceptorship, there is evidence that preceptorship and the role of preceptor in clinical nursing education are not clearly understood or supported. Objectives: To develop a preceptorship model to facilitate clinical nursing education in Botswana. Method: The model development in this study followed the steps of theory generation as described by Chinn and Kramer. These four steps are concept analysis, relationship statements, description and critical reflection of the model. Results: Four main themes emerged from the empirical study that formed the basis for key concepts and model development. The model has six components, namely, agent, recipient, context, procedure, dynamics and terminus. The description of the model is based on Chinn and Kramer. Conclusion: The need for a preceptorship model to facilitate preceptorship cannot be overemphasised in this regard. This model will guide the planning and implementation of preceptorship procedures by different stakeholders to improve its effectiveness in clinical nursing education.